2009
DOI: 10.1002/jlcr.1610
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and preliminary biodistribution in mice of 6‐deoxy‐6‐[131I]iodo‐L‐ascorbic acid

Abstract: An ascorbate analog labeled with iodine-131, 6-deoxy-6-[131 I]iodo-L-ascorbic acid was prepared for evaluation as an in vivo tracer of L-ascorbic acid. The no-carrier-added radiosynthesis was conducted by nucleophilic bromine-iodine exchange between the brominated precursor and sodium [131 I]iodide in 2-pentanone at 130-1401C. HPLC purification using a reversephase column gave 6-deoxy-6-[ 131 I]iodo-L-ascorbic acid in radiochemical yield of 36-60% with high radiochemical purity and satisfactory-specific radioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…Recent studies have shown that high-grade tumor tissue has reduced capacity to accumulate AsA relative to normal tissue. 23) On the other hand, contrary to our expectations, the maximum adrenal uptake of radioactivity (12.52±2.52 ID%/g) was seen at 2 min postinjection, which was 3.9-fold lower than that observed for IAsA in mice at the same time point, 14) and then it rapidly decreased to 2.20±1.44 ID%/g at 30 min after injection with an adrenalto-liver ratio of only 0. 4 IAsA, all of which showed the preferential uptake of radioactivity in the adrenal glands.…”
Section: Resultscontrasting
confidence: 72%
See 3 more Smart Citations
“…Recent studies have shown that high-grade tumor tissue has reduced capacity to accumulate AsA relative to normal tissue. 23) On the other hand, contrary to our expectations, the maximum adrenal uptake of radioactivity (12.52±2.52 ID%/g) was seen at 2 min postinjection, which was 3.9-fold lower than that observed for IAsA in mice at the same time point, 14) and then it rapidly decreased to 2.20±1.44 ID%/g at 30 min after injection with an adrenalto-liver ratio of only 0. 4 IAsA, all of which showed the preferential uptake of radioactivity in the adrenal glands.…”
Section: Resultscontrasting
confidence: 72%
“…There was a somewhat slower clearance of the radioactivity from the blood when compared to 6-18 FAsA 10-13) and 6-131 IAsA 14,15) studied previously. The accumulation of radioactivity in selected organs was highest in the kidneys>liver>lungs>adre nals>heart at 2 min postinjection and then the radioactivity levels gradually decreased with time, similar to those seen for [6][7][8][9][10][11][12][13][14][15][16][17][18] FAsA and 6-131…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…34) To further obtain information on the in vivo behavior of this radiotracer, this paper deals with biodistribution studies in normal rats by both the dissection procedure and whole-body autoradiography. In addition, we performed dis- Normal female rat distribution studies showed high and specific uptake of 6-deoxy-6-[ IAsA while normal adrenal glands showed high uptake of radioactivity, suggesting that these tumors in this model have only a poor transport capacity for this agent.…”
Section: )mentioning
confidence: 99%